2012
DOI: 10.1088/0953-8984/24/24/245901
|View full text |Cite
|
Sign up to set email alerts
|

Soft-mode-driven lattice instabilities in Cs2HgCl4crystal: phenomenological treatment and far-infrared spectroscopy of the structurally modulated phases

Abstract: This paper reports a comprehensive phenomenological description and experimental infrared (IR) investigations of the soft-mode-driven lattice instabilities into various commensurately and incommensurately modulated phases of Cs(2)HgCl(4) crystals. Our theoretical analysis shows that the lattice instabilities along the a and c crystallographic directions are related to low-frequency transverse optical (TO) phonon branches of Σ(2) and Λ(3) symmetry, respectively, which merge together in the center of the Brillou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…According to the difference of crystal structure between the new phase and the parent phase, structural phase transitions can be classified into two types, displacive and reconstructive. Based on the soft mode theory of the displacive phase transformation, Kityk et al [13] studied Pressure-induced ferroelastic instability and lattice dynamics of Cs 2 HgCl 4 crystals, besides, Shchur Ya et al [14] investigated the lattice instabilities into various modulated phases of Cs 2 HgCl 4 crystals. Furthermore, Kityk et al [15] confirmed the elastic instability under hydrostatic pressure is attributed to a critical lowering of a soft optical mode.…”
Section: Introductionmentioning
confidence: 99%
“…According to the difference of crystal structure between the new phase and the parent phase, structural phase transitions can be classified into two types, displacive and reconstructive. Based on the soft mode theory of the displacive phase transformation, Kityk et al [13] studied Pressure-induced ferroelastic instability and lattice dynamics of Cs 2 HgCl 4 crystals, besides, Shchur Ya et al [14] investigated the lattice instabilities into various modulated phases of Cs 2 HgCl 4 crystals. Furthermore, Kityk et al [15] confirmed the elastic instability under hydrostatic pressure is attributed to a critical lowering of a soft optical mode.…”
Section: Introductionmentioning
confidence: 99%